Influence of silica nanoparticles on mass transfer in a membrane-based micro-contactor. Issue 23 (16th February 2016) - Ashrafmansouri, Seyedeh-Saba; Willersinn, Stefan; Esfahany, Mohsen Nasr; Bart, Hans-Jörg
Abstract : Experiments were performed in a membrane based micro-contactor The results showed that nanoparticles are more effective on mass transfer at lower flow rates. Abstract : The EFCE (Europ. Fed. Chem. Engng.) extraction test system of toluene–acetone–water was used, where the organic phase was a toluene-based nanofluid containing 0.001 to 0.1 vol% hydrophobic silica nanoparticles. Experiments were performed in a membrane based micro-contactor at various volumetric flow rates of organic and aqueous phases and with a mass transfer direction from the organic to the aqueous phase. The results showed that nanoparticles are more effective on mass transfer at lower flow rates. A maximum enhancement of about 31% in the overall mass transfer coefficient was observed using 0.001 vol% silica nanoparticles. At higher and lower nanoparticle concentrations, smaller extraction efficiencies were observed. Brownian motion of nanoparticles and induced micro-convection is considered to be responsible for observing mass transfer enhancement at low concentrations of nanoparticles. Also, nanoparticle aggregation and reduction in free volume because of the presence of solid nanoparticles is a possibility for deteriorated mass transfer at higher nanoparticle concentrations.